Золотой ключик, или Приключения Буратино - Толстой Алексей Николаевич (Самовар, 1997)
Экземпляры: М/а ДБ (20130320) / Инвентарный номер: 99529 / Цена: 20 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Т 53 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6